Enfoque metodológico del acompañamiento de la Auditoría de sistemas a una Auditoría Interna en la evaluación de un sistema De información contable. (2021)
The internal audit processes at a general level must be involved, helping, contributing and delivering improvements in the information resources that are carried out within a company, where there is information security and thus avoid the maximum of risks or fraud. In order to give an accurate opinion we must be based on tests and procedures in which samples must be taken and from there to be able to obtain and demonstrate findings, in a systems audit that goes hand in hand with internal control in a company you must have the understanding of general accounting imputation.